Information: Possible worlds and their duals - Sautter, Frank Thomas (Veritas (Porto Alegre), 2020)
Formulations of the classical deductive validity often resort explicitly to modalities: for example, an argument is classically deductively valid if, and only if, necessarily if the premises are true, the conclusion is also true. It is not possible to completely abolish this appeal to modal discourse; inasmuch classical logic is the domain of possibilities. Nevertheless, through an informational semantics, it is possible to avoid that the user of classical logic has to manipulate modalities, although they are somehow imbricated in the infons - minimum information units. From the pioneering work of Carnap and Bar-Hillel, I will present two informational semantics: one directly related to possible worlds, and the other related to the duals of possible worlds.